Evaluation of gas–liquid mass transfer in gas-induced stirred tank reactor using electrical resistance tomography - Abdullah, B. (John Wiley and Sons Ltd, 2017)
BACKGROUND: A gas-entrainment impeller is attractive for multiphase reactive systems such as Fischer–Tropsch reaction and deep liquid-phase oxidation of organics with the possibility of low gas conversion per pass, enhancement of mixing performance and better inter-phase mass transfer compared with conventional impellers. RESULTS: Tomograms obtained from ERT measurement reveal that the conductivity of a gas–water system changes as a function of impeller Reynolds number, ReI. The global gas holdup profile behaviour with ReI exhibited a sigmoid character which was adequately captured by ϵG = ϵG,0 + ϵG,max(1 − exp(−τglReI)). The parity plot showed strong linearity between model predicted and experimental data. The radial gas holdup profiles showed an upward parabolic trend with higher gas holdup values for gas-entrainment impeller systems than the conventional 4-blade impeller. To assess the efficiency of power consumption, the mass transfer coefficient, kLa, for a gas–liquid system in a stirred tank reactor was correlated as a function of dimensionless combination of power number and gas holdup; where α is the bubble collision frequency (s−1) and β is the gas-inducing enhancement factor. CONCLUSION: Three different regimes of volumetric mass transfer coefficient were identified in the stirred tank reactor for each case. Overall, the combination of qualitative and quantitative analyses of ERT along with dissolved oxygen concentration permitted an insightful analysis of the self-gas inducing impeller as a superior mixing technology for potential industrial applications involving gas–liquid operations. © 2017 Society of Chemical Industry. © 2017 Society of Chemical Industry